Identification of DDX31 as a Potential Oncogene of Invasive Metastasis and Proliferation in PDAC - Xie, Yongjie; Liu, Yang; Ding, Jinsheng; Li, Guangming; Ni, Bo; Pang, Huifang; Hu, Xin; Wu, Liangliang (Frontiers in Cell and Developmental Biology, 2022)
ABSTRACT Background: Pancreatic ductal adenocarcinoma (PDAC) is one of the most common malignant tumors worldwide and has poor prognosis. DEAD box proteins participate in cellular processes involving RNA secondary structure changes. However, the functions of DDX31 in PDAC remain to be elucidated. Methods: The key gene DDX31 was identified using a combination of a risk model and weighted gene co-expression network analysis (WGCNA) with R software. The biological functions of DDX31 in PDAC were investigated through bioinformatics analysis and in vitro experiments. Findings: Combining with WGCNA and risk model, DDX31 was identified as a biomarker of the invasive metastasis properties of PDAC, and its expression was closely related to the malignant differentiation of PDAC. The results of gene set enrichment analysis (GSEA) showed that DDX31 was correlated with cell invasive metastasis and proliferation. The inhibition of DDX31 inhibited the invasion and migration of PDAC cells. Survival analysis showed that DDX31 overexpression predicted poor prognosis in patients